Sistem Pendukung Keputusan Siswa SMKN 1 Kota Bengkulu dalam Menentukan Pemilihan Perguruan Tinggi Menggunakan Metode Simple Additive Weighting (SAW) - Apriana, Diwi; Murlena, Murlena; Kaseri, Kaseri; Handayani, Nurfitri; Widyastuti, Rini (Institut Agama Islam Negeri (IAIN) Curup, 2023)
At this time education is very important, in addition to gaining knowledge, the level of education is usually very decisive in finding work and supporting skills, there are many third-grade high school or vocational high school students who find it very difficult to determine which college to choose, this is usually because of the lack of information about the university you want to go to, such as tuition fees, campus facilities, the distance of the campus from the city center, and most importantly, the accreditation of each campus itself. As is known at this time mainly private universities in the city of Bengkulu. Therefore, to solve this problem an appropriate decision support system method is needed to help students. The SAW method is used to determine the selection of tertiary institutions as a process model and the TAM model is used to see responses from respondents based on the influence of acceptance, usability and usefulness variables. From the results of the research conducted, the acceptance rate reached 10.2%, which means that the university selection system using the SAW method is acceptable.